Conflicting theories on addiction aetiology and the strengths and limitations of substance use disorder disease modelling - Greener, Megan R.; Storr, Sarah J. (Frontiers in Molecular Neuroscience, 2023)
A lack of cross-disciplinary unanimity prevails within addiction research. Theories conceptualizing addiction through the three-stage brain disease model contest other theories that substance use disorder is of behavioural or genetic origin. The reverberations of this lack of consensus are noticeable throughout addiction research and within the foundations of disease modelling. The availability of methods to investigate substance use disorder are inconsistent and sometimes unrepresentative. This review discusses theories of addiction aetiology, available models for addiction research and the strengths and limitations of current practical experimental methods of study.